CASHBACK SHOPEE IN THE FIQH TABARRU' PERSPECTIVE - Salsabilla Jasandra Fitricya Zulkarnain (KASBANA, 2023)
Shopee is the e-commerce site with the most visitors in Indonesia; in 2023, it is estimated that Shopee visitors will reach 158 million visitors. A feature that attracts shop visitors is the cashback feature in the form of coins, which can be used as a discount when shopping. This study examines the law of cashback on shops from the fiqh tabarru perspective. Tabarru' is one of the contracts in fiqh muamalah, which does not intend to seek profit. The method used in this study is the descriptive-analytical method, with data collection methods through structured interviews with informants, namely consumers. The results of this study indicate that cashback is categorized as a gift given by the shopee to consumers because they have made a transaction. In the fiqh tabarru’ perspective, gifts are included in gifts, ju'alah, and grants. Grants are gifts with no aim of gaining profit. According to the author's analysis, gifts made by the shopee to consumers are not included in the grant because the shopee does not just provide cashback. However, giving cashback has a purpose: consumers are interested in making transactions on e-commerce shopee, and shopee can benefit from the cashback. In conclusion, from the fiqh tabarru’ perspective, cashback can be included in the gift and ju'alah contracts. Cashback is not included in the grant because the gift given by the shopee contains terms and conditions that apply.